Tharp, Twyla. Keep It Moving: Lessons for the Rest of Your Life. Simon and Schuster, 2019, 190 pages. - Helen Papoulis (Journal of the Assembly for Expanded Perspectives on Learning, 2021)
Tharp, Twyla. Keep It Moving: Lessons for the Rest of Your Life. Simon and Schuster, 2019, 190 pages.
Keywords: Twyla Tharp